Facile Separation of 5‐O‐Galloylquinic Acid from Chinese Green Tea Extract using Mesoporous Zirconium Phosphate. Issue 3 (17th June 2016) - Ma, Yilong; Shang, Yafang; Zhu, Danye; Wang, Caihong; Zhong, Zhifeng; Xu, Ziyang
Abstract: Introduction: 5‐ O ‐Galloylquinic acid from green tea and other plants is attracting increasing attention for its antioxidant and antileishmanial bioactivities. It is always isolated using a silica column, a Sephadex column and high‐performance liquid chromatography (HPLC) methods, which are either laborious or instrument dependent. Objective: To develop a new method to easily separate 5‐ O ‐galloylquinic acid. Methodology: Mesoporous zirconium phosphate (m‐ZrP) was prepared to conveniently separate 5‐ O ‐galloylquinic acid from Chinese green tea extract, and the target compound was easily obtained by simple steps of adsorption, washing and desorption. The effects of the green tea extraction conditions, extract concentrations, and m‐ZrP adsorption/desorption dynamics on the 5‐ O ‐galloylquinic acid separation were evaluated. Results: 5‐ O ‐Galloylquinic acid that was separated from a 70% ethanol extract of green tea was of moderate HPLC purity (92%) and recovery (88%), and an increased non‐specific binding of epigallocatechin gallate (EGCG) on m‐ZrP was observed in the diluted tea extract. The times for maximal adsorption of 5‐ O ‐galloylquinic acid in 70% ethanol extract and maximal desorption of 5‐ O ‐galloylquinic acid in 0.4% phosphoric acid solution were confirmed as 7 h and 5 h, respectively. Conclusion: A facile method to separate 5‐ O ‐galloylquinic acid from Chinese green tea extract using m‐ZrP was established. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A facile method for efficient separation of 5‐ O C‐galloylquinic acid from Chinese green tea extract was developed, and the target compound was obtained by simple steps of m‐ZrP adsorption, deionized water washing and 0.4% phosphoric acid solution desorption. The effects of the green tea extraction conditions, extract concentrations, and m‐ZrP adsorption/desorption dynamics on the 5‐ O ‐galloylquinic acid separation were evaluated. The developed method may facilitate the separation of 5‐ O ‐galloylquinic acid from various plants.